Respirační insuficience, chronická hyperkapnie a domácí neinvazivní ventilace z pohledu pneumologa - Lněnička, Jaroslav (Vnitrni lekarstvi, 2021)
Domiciliary non-invasive ventilation has been an established method of treating chronic hypercapnic respiratory insufficiency for decades. Its effectiveness is based on a number of clinical studies and the prevalence of use worldwide and in the Czech Republic is increasing. The article offers a brief summary of the pathophysiology of hypercapnic respiratory insufficiency and its treatment.
Keywords: non-invasive ventilation; hyperkapnie; neinvazivní ventilace; domiciliary non-invasive ventilation; hypercapnia; lidé; umělé dýchání; chronická obstrukční plicní nemoc; Pulmonary Disease, Chronic Obstructive; Noninvasive Ventilation; Respiration, Artificial; NIV; respiratory insufficiency; Hypercapnia; respirační insuficience; Respiratory Insufficiency; Humans